Low-Dose versus Conventional-dose Oral Isotretinoin Regimens: A Systematic Review on Randomized Controlled Comparative Studies of Different Regimens - Legiawati, Lili; Fahira, Alessa; Taufiqqurrachman, Iqbal; Arifin, Ghafur R.; Widitha, Ucca R. (Current Drug Safety, 2023)
Background: The effectiveness of Isotretinoin is superior compared to other acne therapies, particularly in reducing acne lesion counts. Concerns, however, arise relating to the most optimal dosage regimen with the best efficacy and lesser side effect. Objective: We intend to review existing randomized controlled comparative studies of isotretinoin in different regimens. Methods: PubMed, Cochrane, Scopus, and ScienceDirect were searched. The inclusion criteria is the RCT article. Full-text reading excluded articles that did not use GAGS as the method of measurement. Out of 921 articles that were electronically searched, 6 RCTs were extracted and summarized descriptively. After full-text reading, 4 RCTs were included. We then conducted risk of bias assessments for the selected studies using The Cochrane Risk of Bias Tool. Results: Across all trials, low-dose regimens were preferable in all types of acne-owing to its similar efficacy to conventional dose but with fewer occurrence of side effects as well as better patients’ satisfaction and compliance. Furthermore, a continuous low-dose regimen had the best efficacy in comparison to other regimens of low-dose treatment. Discussion: The limitations of our study include a slight difference in dosage between selected studies. Other limitations are that some studies did not explain the side effects and relapse rate thoroughly and did not state the compliance scoring method used. Conclusion: This review recommends continuous low-dose treatment as the chosen regimen for acne vulgaris. However, further evaluation regarding relapse rate compared to the conventional dose is needed.
Keywords: safety